Parasites of Acestrorhynchus lacustris (Lütken, 1875) (Characiformes: Acestrorhynchidae) collected from the Peixe River, southeast Brazil - Aline de Almeida Camargo; Natacha Heloísa Olavo Pedro; Larissa Sbeghen Pelegrini; Rodney Kozlowiski de Azevedo; Reinaldo José da Silva; Vanessa Doro Abdallah (Acta Scientiarum. Biological Sciences, 2015)
From March to April 2010, specimens of Acestrorhynchus lacustris were collected in the Peixe River, Anhembi, São Paulo State, Brazil.  This characid, commonly known as peixe-cachorro, has a preference for lentic habitats and it features carnivorous habits, with an important role in the food chain. This study aimed to carry out a parasitological analysis of 34 specimens of A. lacustris, and 33 of these were infected by at least one species of metazoan parasite. Nine species were identified: Ameloblastella sp. and Diaphorocleidus sp. (Monogenea); Ascocotyle sp., Diplostomidae gen. sp. and Sphincterodiplostomum musculosum (Digenea); Contracaecum sp., Philometroides caudata, Procamallanus (Spirocamallanus) inopinatus and P. (S.) saofranciscensis (Nematoda). Except P. caudata and P. (S.) saofranciscensis, all parasites showed prevalence higher than 10%. There was a positive correlation between host weight and length and the Ameloblastella sp. Diaphorocleidus sp. was the dominant species. No species was considered central. All parasites showed an aggregated distribution. The parasite community of A. lacustris was characterized by high richness (d = 0.85) and uniformity (J’ = 0.85) and low diversity (HB = 0.56). Except Nematoda, all other parasites were recorded for the first time in this host. Ameloblastella sp., Diaphorocleidus sp. and Ascocotyle sp. are recorded for the first time in the Peixe River.